Pengaruh Motivasi, Budaya Organisasi dan Sistem Informasi Desa terhadap Kinerja Pemerintah Desa - Sudaryati, Dwi; Heriningsih, Sucahyo (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
The objective of this research was to find out the influence of motivation, organizational culture and village information systems on the performance of village government. This research is a quantitative research conducted in Banguntapan District, Bantul Regency. The data were collected by using questionnaires. Respondents in this research are village head and village apparatus. The number of samples in this study is 32. The method of data analysis used is multiple linear regression. The results showed that the Motivation and Information System Village does not affect the Performance of Village Government, while Organizational Culture Influence on Performance of Village Government. This shows that the organizational culture that is formed and there is greatly affect the behavior of members of the organization in carrying out its duties and responsibilities. Good organizational culture will create good village government performance as well.